Storm surge modeling, simulation, and early warning system in the Philippines using ADCIRC + SWAN - Valerio, Alezon Maxine; Garcia, Michael Tyrone; Bongolan, Vena Pearl A. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Back in 2013, Typhoon Yolanda (with international name Haiyan) struck the Philippines and left over 6,000 casualties. Ninety-four percent (94%) of these casualties in Palo and Tacloban City were caused by storm surges. An accurate and time-critical early warning system could have saved thousands of lives by being a crucial factor in a fast and efficient evacuation procedure. However, in the Philippines, there have been little to no advancement in techniques on how to reliably model and present predictions for storm surges, nor ways to disseminate storm surge warnings based from said predictions. This research aims to design and implement an accurate and time-critical early warning system, as well as simulate predicted storm surge occurrences using a cluster-based and task-parallel computation of the coupling of both the Advanced Multi-Dimensional Circulation (ADCIRC) Model and the Simulating Waves Nearshore (SWAN) Model. The early warning system includes a Django-powered website that shows the maximum elevation of the storm surge, as well as inland inundation, in the form of an animation superimposed over a clickable map. A text-messaging module has also been implemented to warn local government units of a storm surge threat at most 48 hours in advance of an incoming typhoon. This will inform respective authorities regarding storm surge threat every two hours after the initial warning and provide backbone to crucial evacuation efforts.
Thesis (Bachelor of Science in Computer Science)--University of the Philippines Diliman
Keywords: Storm surges -- Mathematical models. -- Philippines